KETERKAITAN ANTARA CITRA DESTINASI, PERSEPSI NILAI PENGALAMAN DAN KEPUASAN WISATAWAN KULINER - Heri Setiawan (Universitas Mercu Buana, 2018)
Culinary tourism is part of tourism activities that continue to grow in Indonesia, but studies on culinary tourism are still rarely. The purpose of the study is to analyze the relationship among the image of a tourism destination, experiential value perception with tourist satisfaction while in the culinary attractions. The study was conducted in Palembang City which is known as a city with a variety of typical traditional foods. The research data was obtained by distributing questionnaires to 140 local tourists who visited culinary attractions in Palembang City. Data analysis was carried out using path analysis method with data processing software namely AMOS and SPSS. Research findings state that the image of tourism destinations has a relationship with the experiential value perception significantly. Then, the experiential value perception has a relationship with tourist satisfaction significantly and the image of tourism destinations has a relationship with tourist satisfaction significantly. Implications of research results can be useful for referrals for other researchers or parties interested in culinary tourism destinations